2020
DOI: 10.1038/s41467-019-14079-0
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Genome Reference Bank contains whole genome and phenotype data of 2570 healthy elderly

Abstract: Population health research is increasingly focused on the genetic determinants of healthy ageing, but there is no public resource of whole genome sequences and phenotype data from healthy elderly individuals. Here we describe the first release of the Medical Genome Reference Bank (MGRB), comprising whole genome sequence and phenotype of 2570 elderly Australians depleted for cancer, cardiovascular disease, and dementia. We analyse the MGRB for single-nucleotide, indel and structural variation in the nuclear and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 71 publications
2
68
0
2
Order By: Relevance
“…Overall, our results are concordant with the recent study on 2570 healthy elderly within the Medical Genome Reference Bank in Australia [ 13 ]. In that study, the participants did not have any personal history of cancer, cardiovascular disease, or dementia, while our study participants did not have any personal or family history of cancer in one or two older and younger generations that included around 1000 cancer-free individuals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, our results are concordant with the recent study on 2570 healthy elderly within the Medical Genome Reference Bank in Australia [ 13 ]. In that study, the participants did not have any personal history of cancer, cardiovascular disease, or dementia, while our study participants did not have any personal or family history of cancer in one or two older and younger generations that included around 1000 cancer-free individuals.…”
Section: Discussionsupporting
confidence: 92%
“…A three-generation analysis in the Swedish Family-Cancer Database found that 16% of cancers were diagnosed in the third generation individuals whose two older generations were cancer-free, yet the relative risk (RR) of 0.9 showed no dramatic protection [ 12 ]. Recently, a whole-genome sequencing (WGS) project among 2570 healthy elderly within the Medical Genome Reference Bank in Australia reported fewer disease-associated common and rare germline variants compared to both cancer cases and the gnomAD and UK biobank cohorts [ 13 ]. Here, we identified 51 elderly cancer-free index persons (born in the 1920s or 1930s) whose siblings and relatives in one or two older and younger generations were cancer-free.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pathogenicity assertions must be interpreted based on specific population datasets. Also, regarding P/LP asserted variants in the 59 ACMG actionable genes list (Supplementary Table 11), 14 were found in 1.2% of individuals 26 comparable to the Australian elderly cohort 17 .…”
Section: Clinically Relevant Findingsmentioning
confidence: 97%
“…For variants associated with monogenic late-onset disorders, unaffected elderly individuals serve as a proper control group to improve diagnosis accuracy. This rationale was previously explored by us using whole-exome sequencing of elderly Brazilians 16 , and by others using a European-descent whole-genome dataset of Australian elderly 17 .…”
Section: Introductionmentioning
confidence: 99%
“…485 patients were referred to the Genome.One diagnostic laboratory for genomic testing (including CNV analysis) in a clinical setting, and do not have consent for the release of raw or processed genomic data. WGS data from 500 healthy controls were provided by the Medical Genomics Reference Bank (MGRB) [36,37]. This research was approved by the ethics committee from the Royal Prince Alfred Hospital, Sydney, Australia (HREC ref no.…”
Section: Reference Materials Patient Recruitment and Ethical Compliancementioning
confidence: 99%